It takes two to tango: Preschool siblings' musical play and prosociality in the home. Issue 4 (30th January 2020) - Cirelli, Laura K.; Peiris, Rachel; Tavassoli, Nasim; Recchia, Holly; Ross, Hildy
Abstract: In childhood, musical play is an important part of home life and, potentially, sibling play. Considering the social–emotional relevance of musical activities, siblings' engagement in musical play may also be associated with social development. The current longitudinal study examined musical play in 39 pairs of siblings during naturalistic home play at two time points: (a) when siblings were 2 and 4 years old (T1), and (b) 2 years later when siblings were 4 and 6 years old (T2). Musical play, especially singing and dancing, was more prevalent at T2. Birth order effects were also revealed; 4‐year‐old second‐borns (T2) engaged in more solo musical play than 4‐year‐old firstborns (T1), but 4‐year‐old firstborns initiated joint musical play more often than 4‐year‐old second‐borns. Associations between musical play and prosociality also emerged. Specifically, both older and younger siblings' rates of prosociality correlated positively with older sibling musical play at each time point. These findings reveal intriguing effects of age and birth order on both solo and joint musical play between siblings, and highlight a potential link between spontaneous musical play in the home and social development.